Analysis of the immune response of human dendritic cells to Mycobacterium tuberculosis by quantitative proteomics. Issue 1 (December 2016) - Kuo, Chiu-Ping; Chang, Kuo-Song; Hsu, Jue-Liang; Tsai, I-Fang; Lin, Andrew; Wei, Tsai-Yin; Wu, Chien-Liang; Lu, Yen-Ta
Abstract Background The cellular immune response forMycobacterium tuberculosis (M. tuberculosis ) infection remained incompletely understood. To uncover membrane proteins involved in this infection mechanism, an integrated approach consisting of an organic solvent-assisted membrane protein digestion, stable-isotope dimethyl labeling and liquid chromatography-tandem mass spectrometry (LC-MS/MS) analysis was used to comparatively profile the membrane protein expression of human dendritic cells upon heat-killedM. tuberculosis (HKTB) treatment. Results Organic solvent-assisted trypsin digestion coupled with stable-isotope labeling and LC-MS/MS analysis was applied to quantitatively analyze the membrane protein expression of THP-1 derived dendritic cells. We evaluated proteins that were upregulated in response to HKTB treatment, and applied STRING website database to analyze the correlations between these proteins. Of the investigated proteins, aminopeptidase N (CD13) was found to be largely expressed after HKTB treatment. By using confocal microscopy and flow cytometry, we found that membranous CD13 expression was upregulated and was capable of binding to live mycobacteria. Treatment dendritic cell with anti-CD13 antibody duringM. tuberculosis infection enhanced the ability of T cell activation. Conclusions Via proteomics data and STRING analysis, we demonstrated that the highly-expressed CD13 is also associated with proteins involved in the antigen presenting process, especially with CD1 proteins. Increasing expression of CD13 on dendritic cells whileM. tuberculosis infection and enhancement of T cell activation after CD13 treated with anti-CD13 antibody indicates CD13 positively involved in the pathogenesis ofM. tuberculosis.